(Dis)harmony between Deuteronomy 22,23-29 and 2 Samuel 13 - Kim, Daewook (Biblica, 2024)
The lexical and thematic similarities between Deut 22,23-29 and 2 Samuel 13 suggest the intertextual relationships between them. The narrative of 2 Samuel 13 contains specific claims that Deut 22,23-29 does not describe, and thus it seems that the author(s) of 2 Samuel 13 recognized and employed Deut 22,23-29. The author(s) of 2 Samuel 13 combined the ideal and real through (dis)harmony with Deut 22,23-29, thereby encouraging communal unity and protecting the community in the social circumstances of varied conflicts that occurred during the Persian period.